3D-printed TCP-HA scaffolds delivering MicroRNA-302a-3p improve bone regeneration in a mouse calvarial model - Pirawish Limlawan; Numpon Insin; Laurine Marger; Mélanie Freudenreich; Stéphane Durual; Anjalee Vacharaksa (Nature Publishing Group, 2023)
Abstract Objective To demonstrate hydroxyapatite nanoparticles modified with cationic functional molecules. 3-aminopropyltriethoxysilane (HA-NPs-APTES) carrying microRNA-302a-3p (miR) in the 3D-printed tricalcium phosphate/Hydroxyapatite (TCP/HA) scaffold can increase healing of the critical-sized bone defect. Materials and methods 3D-printed TCP/HA were modified with HA-NPs-APTES by two methods (M1, M2). The dispersion of particles was visualized by fluorescent microscopy. Biocompatibility of the scaffolds was tested by alizarin assay. Delivery of miR to the cells and osteogenic gene expression were evaluated by qPCR. After selecting best method (M2), scaffolds, scaffolds+HA-NPs-APTES with or without miR were implanted in 4 mm mouse calvarium defect (n = 4 per group). After 2,4 and 6 weeks, bone regeneration were evaluated by microCT and histology sections. Results Both M1 and M2 scaffolds were biocompatible with cell adhesion on its surface. M2 scaffold showed significant increase of miR, suggesting successful delivery, resulted in downregulation of its target mRNA COUP-TFII, and upregulation of RUNX2 mRNA. Calvarium defect with M2 scaffold also showed significantly higher BV/TV and higher number of filled spaces at all time points. Histomorphometry demonstrated new bone formed at the center of the HA-NPs-APTES-miR scaffold earlier than controls. Conclusion TCP/HA scaffold modified with HA-NPs-APTES facilitated delivery of miR and enhanced bone regeneration.